Dual-bond fracture metamaterials with full-field extrinsic toughening - Zhiqiang Meng; Peidong Lei; Boyuan Hou; Bin Liu; Yifan Wang (Nature Communications)
Abstract Fracture resistance presents a pivotal challenge in mechanical metamaterials, as traditional designs often fail to mitigate crack propagation and enhance energy dissipation. Despite efforts to enlarge the fracture process zone, energy dissipation remains highly localized near the crack tip, restricting improvements in fracture toughness. This study introduces dual-bond fracture metamaterials that integrate weak and strong bonds to achieve full-field energy dissipation before crack propagation. Through the sequential breaking of weak bonds and the formation of plastic hinges, these materials redistribute stress across the entire structure, significantly expanding the fracture process zone and enhancing toughness. The specific fracture energy, a metric we propose to characterize structural fracture resistance, is governed by extrinsic energy dissipation and scales linearly with specimen size. Additionally, the concept of an equivalent force concentration factor is introduced to characterize fracture behavior in dual-bond fracture metamaterials. Gradient designs further enable asymmetric fracture sensitivity and surface crack shielding, thereby improving resilience in defect-prone environments. These metamaterials offer versatility, with potential applications in protective nets, shock absorbers, and blast containment vessels. Finally, the dual-bond design can be realized with a variety of materials, highlighting its generality and broad applicability for diverse engineering applications.